2016
DOI: 10.1002/chem.201600393
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Alkene Difunctionalization with Nitrenes

Abstract: The Rh(II) -catalyzed oxyamination and diamination of alkenes generate 1,2-amino alcohols and 1,2-diamines, respectively, in good to excellent yields and with complete regiocontrol. In the case of diamination, the intramolecular reaction provides an efficient method for the preparation of pyrrolidines, and the intermolecular reaction produces vicinal amines with orthogonal protecting groups. These alkene difunctionalizations proceed by aziridination followed by nucleophilic ring opening induced by an Rh-bound … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 131 publications
1
30
0
Order By: Relevance
“…It reported the ring-opening reaction of that aziridine needed harsh reaction conditions. [11,15] Indeed, under the optimized reaction conditions, the target aziridine 11 was isolated in 57% yield, demonstrating aziridine was the real intermediate. Finally, a radical probe experiment was performed by submitting of TEMPO (1.0 equiv) into the optimized reaction conditions (Scheme 7, D).…”
Section: Resultsmentioning
confidence: 93%
“…It reported the ring-opening reaction of that aziridine needed harsh reaction conditions. [11,15] Indeed, under the optimized reaction conditions, the target aziridine 11 was isolated in 57% yield, demonstrating aziridine was the real intermediate. Finally, a radical probe experiment was performed by submitting of TEMPO (1.0 equiv) into the optimized reaction conditions (Scheme 7, D).…”
Section: Resultsmentioning
confidence: 93%
“…In 2014, the terminal alkenes were also oxyaminated under similar reaction conditions . Mechanistic studies showed that this catalytic cycle involved a key rhodium‐bound nitrene intermediate, which played a dual role by allowing the expected alkene aziridination and then acting as a Lewis acid to activate the aziridine towards the attack of nucleophiles …”
Section: Other Transition‐metal Catalystsmentioning
confidence: 99%
“…[89] Mechanistic studies showedt hat this catalytic cycle involved ak ey rhodium-bound nitrene intermediate, which played ad ual role by allowing the expected alkene aziridinationa nd then acting as aL ewis acid to activate the aziridine towards the attack of nucleophiles. [90] This three-componentd ifunctionalization of alkenes could also be mediated by,f or example, Fe, [91] Ag, [92] Co, [93] Mn, [94] and so on. [95] Various functionalized alkanes were readily synthesized by those methods.…”
Section: Other Transition-metal Catalystsmentioning
confidence: 99%
“…The inspection of NMR spectroscopic data clearly showed that compound 3 results from the aziridine ring-opening by pivaloic acid released from the iodine (III) oxidant, as previously reported by one of us. [21] The aziridine opening at C- 13 The amination reaction of 11,13-Dihydroachalensolide under these conditions afforded the sole compound 4 with 5 % yield. Analysis of the NMR spectra showed the disappearance of one methine from the substrate and the presence of a quaternary carbon at δ 70.1 assigned to the C-1 position.…”
mentioning
confidence: 99%
“…The inspection of NMR spectroscopic data clearly showed that compound 3 results from the aziridine ring-opening by pivaloic acid released from the iodine (III) oxidant, as previously reported by one of us. [21] The aziridine opening at C-13 was proposed based on the appearance of the signals corresponding to the pivaloyloxy group [δ H 1.24 (s, H 3 -3''), δ C 177.4 (C-1''), δ C 39.0 (C-2''), and δ C 27.2 (C-3'')] and the upfield shifts of the CH 2 -13 methylene signals from δ C 36.6, δ H 3.10, and δ H 2.99 for compound 2 to δ C 64.3, δ H 4.53, and δ H 4.39 for compound 3. The pattern of substitution at C-11 was confirmed through the correlation observed in the HMBC spectrum between H 2 -13 and C-12 (δ 172.7) and C-1'' (δ 177.4) (see Figure S11 Supporting Information).…”
mentioning
confidence: 99%